Rest Area Di Jalan Lintas Pekanbaru-Dumai Dengan Pendekatan Arsitektur Hijau - Winata, Hendika Yurnas; Hidayat, Wahyu; Amanati, Ratna (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Cross street is a path Pekanbaru-Dumai in Riau Province's economy to the level of traffic density is high enough. This resulted in increased levels of accident-prone. So necessary to have a public facilities such as rest area equipped with facilities to make it easier for drivers and passengers in motor vehicles are traveling. To respond to the emergence of environmental issues that lead to global warming then encourage green architecture to be a movement in the field of architecture and the built environment to respond to the impact of environmental conditions that occur at this time. Then the existing problems, namely how to design a building that is able to accommodate the rest area needs road users in highway Pekanbaru-Dumai and applying green architecture design strategy according to Allison G. Kwok into the rest area building design. The concept is appointed for building the rest area are earth friendly is the development of the principles of green architecture. The method used is the strategy in the design of green architecture that is envelope, lighting, cooling, energy production, water and waste. So that can be a container for road users who are traveling as well as to reduce environmental damage due to global warming.Keywords: Rest Area, Earth Friendly, Green Architecture